2015
DOI: 10.1038/srep12138
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inhibition Of The Ubiquitin Ligase Rnf5 Attenuates Phenotypes Associated To F508del Cystic Fibrosis Mutation

Abstract: Cystic fibrosis (CF) is caused by mutations in the CFTR chloride channel. Deletion of phenylalanine 508 (F508del), the most frequent CF mutation, impairs CFTR trafficking and gating. F508del-CFTR mistrafficking may be corrected by acting directly on mutant CFTR itself or by modulating expression/activity of CFTR-interacting proteins, that may thus represent potential drug targets. To evaluate possible candidates for F508del-CFTR rescue, we screened a siRNA library targeting known CFTR interactors. Our analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 61 publications
10
65
0
Order By: Relevance
“…Western blot performed on the biotinylated fraction with the CFFT 596 antibody revealed that, in cells expressing WT CFTR, the mature form was prevalent, while cells expressing F508del-CFTR expressed minor levels of immature CFTR on their surface ( Figure 5D). This is not surprising, as it has been demonstrated that immature CFTR can traffic to the plasma membrane through the unconventional secretion route (39,49). Importantly, the levels of mature CFTR available for biotinylation were markedly increased following treatment with VX-809 in F508del-CFTR-expressing cells ( Figure 5D).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencmentioning
confidence: 59%
See 3 more Smart Citations
“…Western blot performed on the biotinylated fraction with the CFFT 596 antibody revealed that, in cells expressing WT CFTR, the mature form was prevalent, while cells expressing F508del-CFTR expressed minor levels of immature CFTR on their surface ( Figure 5D). This is not surprising, as it has been demonstrated that immature CFTR can traffic to the plasma membrane through the unconventional secretion route (39,49). Importantly, the levels of mature CFTR available for biotinylation were markedly increased following treatment with VX-809 in F508del-CFTR-expressing cells ( Figure 5D).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencmentioning
confidence: 59%
“…We performed functional analysis of Tα-1 activity as F508del-CFTR corrector by means of the microfluorimetric assay based on the HS-YFP that has been extensively used to investigate various rescue maneuvers (36)(37)(38)(39)(40) and by means of whole-cell patch-clamp analyses. In parallel, we also performed immunolocalization experiments and biochemical analyses of the electrophoretic mobility of the different CFTR forms expressed by the cells under resting conditions or following treatment with Tα-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the other five eGenes, including HLA-DRA (the most strongly associated), APOM, DXO, RNF5 and TAP1 were novel, i.e., had not been identified in GWAS. Interestingly, the association of RNF5 was consistent with its function as a regulator of the CFTR protein and suggested role in cystic fibrosis (Sondo et al, 2018;Tomati et al, 2015). We next identified four novel eGenes (EHMT2, GPANK1, HLA-C and RNF5) associated with weight phenotypes.…”
Section: Regulatory Variants In the Mhc Region Play Important Roles Imentioning
confidence: 56%